The plant tissue culture collection at the Department of Botany, University of Debrecen - Máthé, Csaba (Acta Biologica Szegediensis, 2012)
We present a list of tissue culture systems developed at the Department of Botany, University of Debrecen. Several of tissue cultures were developed for the first time in our laboratory. These include micropropagation of Elatine hungarica, callus cultures of several oak genotypes of Hungarian origin and of Crocus species characteristic for the Carpathian Basin. Callus cultures were either organogenic (e.g. Crocus scepusiensis) or embryogenic (Quercus petraea, Galanthus and Crocus species, Phragmites australis). In case of embryogenic cultures, somatic embryos showed either normal, bipolar development (e.g. Crocus heuffelianus, Phragmites australis) or they have lost this bipolarity at the maturation of embryos (C. banaticus, C. sativus,Galanthus). The type of callus is yet to be identified for several cultures (e.g. Plantago lanceolata, Vicia faba). Most of our in vitro cultures proved to have plant regeneration potential. Several of them derived from endangered/ red list plants (Crocus species, Elatine hungarica, Galanthus nivalis), therefore they are suitable for germplasm preservation. Others (Quercus, Phragmites australis) proved to be suitable for stress physiology and/ or cell biology experiments. Cultures such as Crocus sativus or Plantago lanceolata derived from plants of medicinal importance, therefore are of potential pharmacological use.